A SAXS study of PHB/DGEBA blends crystallized at different temperatures - Tognana, Sebastian Alberto (2015)
A small-angle X-ray scattering (SAXS) study of blends of poly-3-hydroxybutyrate (PHB)/diglycidyl ether of bisphenol A (DGEBA) with weight ratios of 90/10, 70/30 and 50/50 and PHB isothermally crystallized at temperatures between 60ºC and120ºC for one hour was performed. PHB was studied at different temperatures between 30ºC and 140ºC. The scattering curve results (intensity as a function of scattering vector (q)) indicated a main peak and secondary peaks associated with the thickness of the lamellae of PHB (with a strong tendency to crystallization). The position of the main peak decreased when the temperaturewas increased. At high temperatures (~120ºC), a deformation was observed in the main peak and a secondary peak was superimposed. This secondary peak was associated with the lamellar structures formed during the re-crystallization process. The results are discussed based on the DGEBA inclusion in the blends, crystallization temperature and partial interlamellar segregation.